PENGARUH HARGA, KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA CV. DUNIA INDAH FURNITURE DESA TERU - Rikard Sinaga; Zufriady Zufriady (LPPM STIE PERTIBA Pangkalpinang, 2020)
This study aims to analyze and determine the effect of Price, Product Quality, and Promotion on Purchase Decisions at CV. Teru Furniture World Beautiful Village. The research variables consist of independent variables, namely: price, product quality, and promotion, while the dependent variable is purchasing decisions. The data analysis used was multiple regression analysis and continued with simultaneous and partial hypothesis testing with the help of the SPSS program. The results showed that the price had an effect on purchasing decisions, product quality had an effect on purchasing decisions, and promotions had an effect on purchasing decisions, while all the independent variables together influenced purchasing decisions. The results of the hypothesis test show that the null hypothesis (H0) for the price and promotion variables is rejected and the alternative hypothesis (Ha) is accepted, meaning that the price and product quality variables affect the purchasing decision variables, while the product quality variable answers the null hypothesis (H0) is accepted and (Ha) ) rejected means that the product quality variable has no effect on the purchasing decision variables